2018
DOI: 10.2147/ott.s159979
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin-driven adrenocortical carcinoma is characterized with immune exclusion

Abstract: AimAdrenocortical carcinoma (ACC) is characterized by overexpressed CTNNB1, which is reported to modulate immune exclusion. Cross talk between CTNNB1 and cancer immunity in ACC remains unclear.Materials and methodsIn silico reproduction of TCGA-ACC dataset (N = 92) and external validation using tissue samples were performed (N = 16). Expression data of CTNNB1, PD-1, and PD-L1 were extracted in silico and tumor-infiltrating lymphocytes (TILs) were profiled using code provided by Tumor IMmune Estimation Resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…Therefore, either overactivation of the Wnt/ β -catenin pathway or loss of p53 is potential tumor-intrinsic factors that, altering on the ability of ACC cells to recruit BAFT3 DC cell and leading to T-cell exclusion, likely indicate that this type of tumor is potentially resistant to immunotherapy. This point is strengthened by results reported on CTNNB1 expression and T-cell infiltration that have been investigated in a series of ACC tumors, showing that the increased CTNNB1 expression correlated with reduced infiltration in T cells [40]. Interestingly, high levels of CTNNB1 expression have been associated as well with increased cortisol levels [40] that likely contribute to the clinical resistance of ACC to immunotherapy [41].…”
Section: Immunologic Properties Of Accmentioning
confidence: 93%
“…Therefore, either overactivation of the Wnt/ β -catenin pathway or loss of p53 is potential tumor-intrinsic factors that, altering on the ability of ACC cells to recruit BAFT3 DC cell and leading to T-cell exclusion, likely indicate that this type of tumor is potentially resistant to immunotherapy. This point is strengthened by results reported on CTNNB1 expression and T-cell infiltration that have been investigated in a series of ACC tumors, showing that the increased CTNNB1 expression correlated with reduced infiltration in T cells [40]. Interestingly, high levels of CTNNB1 expression have been associated as well with increased cortisol levels [40] that likely contribute to the clinical resistance of ACC to immunotherapy [41].…”
Section: Immunologic Properties Of Accmentioning
confidence: 93%
“…As a convenient web-based resource, TIMER can also make the relationship between gene expression and tumor purity in cancer visible [27]. The gene module on TIMER estimates the correlation between gene expression and tumor-infiltrating immune cells (TIICs) [28]. Based on TIMER, we analyzed the relationship between STAT3 expression and tumor purity in diverse cancer types.…”
Section: Timer Databasementioning
confidence: 99%
“…In the tumor microenvironment, the immunosuppressive and immunostimulating signatures have a potential prognostic value for some cancer types [9,10]. Recently, Liu et al reported that CD8 + T cells and expression of programmed death ligand 1 (PD-L1/B7-H1) were significantly associated with improved survival, indicating a potential role for the immune signature in the assessment of ACC prognosis [11]. However, PD-L1 is reportedly only expressed in approximately 10% of ACC tumor cells and cell membranes [12,13].…”
Section: Introductionmentioning
confidence: 99%